2019
DOI: 10.5194/acp-2019-201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Southern Ocean cloud in the HadGEM3 general circulation model and MERRA-2 reanalysis using ship-based observations

Abstract: Southern Ocean (SO) shortwave (SW) radiation biases are a common problem in contemporary general circulation models (GCMs), with most models exhibiting a tendency to absorb too much incoming SW radiation. These biases have been attributed to deficiencies in the representation of clouds during the austral summer months, either due to cloud cover or cloud optical thickness being too low. The problem has been the focus of many studies, most of which utilised satellite datasets for model evaluation. We use multi-y… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…It has been well established that there is currently a large shortwave radiation bias over the Southern Ocean (Bodas‐Salcedo et al, ). Observations of cloud base height from radiosondes and ceilometer measurements throughout this same voyage showed that the shortwave radiation bias is related to the lack of low‐level cloud and fog predicted within atmospheric models (Kuma et al, ). Therefore, it is reasonable to expect that even with an improved in‐cloud activation scheme (e.g., Grythe et al, ), FLEXPART‐WRF still would have underestimated the frequency of droplet activation events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that there is currently a large shortwave radiation bias over the Southern Ocean (Bodas‐Salcedo et al, ). Observations of cloud base height from radiosondes and ceilometer measurements throughout this same voyage showed that the shortwave radiation bias is related to the lack of low‐level cloud and fog predicted within atmospheric models (Kuma et al, ). Therefore, it is reasonable to expect that even with an improved in‐cloud activation scheme (e.g., Grythe et al, ), FLEXPART‐WRF still would have underestimated the frequency of droplet activation events.…”
Section: Resultsmentioning
confidence: 99%
“…It is useful, however, to recall that clouds over the Southern Ocean are not very well represented within modern atmospheric models (Schuddeboom et al, 2019;Trenberth & Fasullo, 2010). Current era atmospheric models systematically underpredict the amount of low-lying cloud and fog relative to the true cloud observed over the Southern Ocean (Kuma et al, 2019). Hence, even if a state-of-the-art microphysical parameterization of in-cloud scavenging had been present in FLEXPART-WRF, it is likely that the scavenging of sea spray still would have been underestimated.…”
Section: Meteorological Measurementsmentioning
confidence: 99%
“…propane, formaldehyde, acetaldehyde, acetone, NH 3 , black carbon and organic carbon were prescribed based on the year 2000 (Lamarque et al, 2010). A further eight sensitivity simulations were performed, each of 10-year duration, from 1989 to 1998.…”
Section: Simulations Performedmentioning
confidence: 99%
“…Turnock et al (2019) show that the effect of pH on particles larger than 50 nm in diameter (which may activate to CCN) over the Southern Ocean is not negligible. Aqueous-phase chemistry may also be affected in the model due to the lack of persistent low-lying cloud over the Southern Ocean (Kuma et al, 2019). Aqueous-phase chemistry is more efficient at processing sulfur-containing gases than gas-phase chemistry, but cloud droplets are needed to allow in-cloud droplet chemistry to occur.…”
Section: Dms Oxidation Chemistrymentioning
confidence: 99%